Effects of CeO2 doping on the structural and mechanical properties of MgO-ZrO2 ceramic - Bogñalbal, Eufrecina B.
MgO-ZrO2 ceramic specimens containing 9.7 mole% MgO and 90.3 mole% ZrO2 and doped with varying amounts of CeO2 ranging from 0 mole% to 24 mole% were sintered by solid state method at 1300 degree Celsius to 1500 degree Celsius for varying times of 1 to 6 hours and subjected to various characterization procedures. The phases formed were strongly dependent on composition and temperature but independent of time. The lattice parameter of cubic stabilized zirconia samples sintered at 1500 degree Celsius decreased linearly with CeO2 concentration in accordance with the Vegard's law. SMA and SEM analysis revealed equiaxed grains for all samples. Measurements taken from SEM characterization showed that grain size increases with sintering temperature and time; the average grain size ranged from -0.5 um at 1300 degree Celsius for single phase monoclinic ZrO2 containing 0% mole CeO2 to -7 um at 1500 degree Celsius for single phase cubic ZrO2 containing 24% mole CeO2. The microstructures of two and three phase samples contained larger cubic ZrO2 grains compared to tetragonal and monoclinic ZrO2 grains. The % shrinkage of the sintered specimens increased linearly with time. However, the shrinkage decreased linearly with CeO2 concentration, a behavior attributed to the decrease in the atomic packing factor as a result of lattice expansion due to addition of cerium having larger radius than zirconium. The hardness increased linearly with square root of CeO2 concentration at compositions less than 12% mole CeO2, a behavior attributed to solid solution strengthening; hardness decreased linearly with CeO2 concentration above 12% mole CeO2 due to the change in the chemical character of the ceramic with CeO2 addition. The low hardness values at lower CeO2 concentrations and temperatures are due to lower density contributed by microcracks in monoclinic ZrO2. Highest hardness (11 GPa) was obtained by single-phase cubic ZrO2 at composition containing 12% mole CeO2 sintered at 1500 degree Celsius. The fracture toughness increased linearly with CeO2 content up to a concentration containing the maximum amount of tetragonal phase then dropped with further CeO2 addition. The increase in the fracture toughness is attributed to transformation toughening while the drop in the fracture toughness at higher CeO2 concentrations is due to the increasing cubic character of the ceramic. Peak fracture toughness values shifted to lower CeO2 concentrations with increase in temperature. Highest fracture toughness value (7 MPa.m1/2) was obtained in tetragonal + cubic ZrO2 phase at composition containing 12% mole CeO2 sintered at 1300 degree Celsius